Penile doppler ultrasound predicts cardiovascular events in men with erectile dysfunction. (8th November 2018) - Caretta, N.; De Rocco Ponce, M.; Minicuci, N.; Palego, P.; Valente, U.; Garolla, A.; Ferlin, A.; Foresta, C.
Abstract: Background: Traditional risk factors used to assess cardiovascular risk miss a significant population who are indeed at risk for future cardiac events. Erectile dysfunction (ED) is an emerging marker for future cardiovascular disease (CVD) and major adverse cardiovascular events (MACE), especially in young and middle‐aged men with vasculogenic ED. Cavernous arteries morphological alterations at penile colour doppler ultrasound (P‐CDU) are used to find a vasculogenic ED. Objectives: We investigated the possible relationship between cavernous arteries morphological alterations at P‐CDU assessment and future MACE. Materials and methods: We conducted a retrospective cohort study involving 300 ED patients, aged 35–65 years (mean age 54.1 ± 7.1), with a follow‐up period of 10 years. Patients underwent vascular evaluation including P‐CDU, colour doppler ultrasound of the carotid and lower limbs arteries. At baseline data for glucose metabolism, lipid profile, hypertension and hormonal status were collected. During the follow‐up period, the occurrence of MACE was evaluated. Results: We found a strong association between cavernous arteries morphological alterations and CVD with a threefold increased risk of future MACE in comparison to patients with healthy cavernous arteries (RR 3.2, 95% CI 1.17–8.78). This association remained statistically significant after adjustment for CV risk factors (age, glycaemia, total cholesterol, hypertension and smoke). Conclusions: Morphological alterations of cavernous arteries are independently associated with an increased risk of future MACE. These data contribute to the formulation of the hypothesis that cavernous artery pathology at P‐CDU is related to MACE.